Identification and virulence screening of fungal and bacterial entomophathogens of the edible long-horned grasshopper Ruspolia differens (Orthoptera: Tettigoniidae) from Uganda - Leonard, Alfonce; Egonyu, James Peter; Khamis, Fathiya; Tanga, Chrysantus; Ekesi, Sunday; Kyamanywa, Samuel; Subramanian, Sevgan (African Entomology, 2023)
Natural enemies are major challenges in laboratory rearing of grasshoppers, but the identity and virulence of these towards the edible long-horned grasshopper Ruspolia differens (Serville) is scarcely known. In this study, fungi and bacteria were isolated from R. differens collected from Mbarara, Masaka, Hoima, Kampala and Kabale districts in Uganda in 2018, cultured on standard microbial media, identified using molecular techniques and screened for virulence against the insect in laboratory bioassays. Fourteen and nine species of fungi and bacteria were isolated from R. differens, respectively, with the number of isolates varying based on collection site. The most prevalent entomopathogenic fungal species were Aspergillus flavus Link (27.3%), Fusarium equiseti (Corda) (24.2%), Mucor fragilis Fresen (12.1%), Clonostachys rosea (Link) (6.0%) and Aspergillus tamarii Kita (6.0%); whereas the most prevalent bacterial isolates were Serratia marcescens Bizio (38.1%), Bacillus thuringiensis (Berliner) (14.3%) and Enterobacter cloacae (Jordan) (14.3%). Nine of the fungal species namely Clavispora lusitaniae Rodrigues de Miranda, Lichtheimia corymbifera (Cohn), Trichoderma koningii Oudem, F. equiseti, M. fragilis, Aspergillus niger van Tieghem, Epicoccum sorghinum (Saccardo), C. rosea, Penicillium commune Charles Thom; and five bacterial species (Proteus penneri Hickman, S. marcescens, B. thuringiensis, Staphylococcus sciuri Kloos and Enterococcus faecalis (Andrewes and Horder)) were ~5–7-fold and ~4–5-fold, more lethal to third instars of R. differens than untreated controls, respectively. This study is the first to report C. lusitaniae, Exserohilum mcginnis Padhye and Ajello, E. sorghinum, P. penneri and E. cloacae as insect pathogens. The results suggest a need to quarantine field collected R. differens before introducing them into the insectary, as well as performing antimicrobial practices during rearing of the insect to prevent entomopathogen-based mortality.